Class and compassion: socioeconomic factors predict responses to suffering - Stellar, Jennifer E; Manzo, Vida M; Kraus, Michael W; Keltner, Dacher (Emotion (Washington, D.C.), 2012)
Previous research indicates that lower-class individuals experience elevated negative emotions as compared with their upper-class counterparts. We examine how the environments of lower-class individuals can also promote greater compassionate responding-that is, concern for the suffering or well-being of others. In the present research, we investigate class-based differences in dispositional compassion and its activation in situations wherein others are suffering. Across studies, relative to their upper-class counterparts, lower-class individuals reported elevated dispositional compassion (Study 1), as well as greater self-reported compassion during a compassion-inducing video (Study 2) and for another person during a social interaction (Study 3). Lower-class individuals also exhibited heart rate deceleration-a physiological response associated with orienting to the social environment and engaging with others-during the compassion-inducing video (Study 2). We discuss a potential mechanism of class-based influences on compassion, whereby lower-class individuals' are more attuned to others' distress, relative to their upper-class counterparts.